2005
DOI: 10.1002/app.21624
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of acetyl ferrocene migration from hydroxyl‐terminated polybutadiene based elastomers by means of ultraviolet–visible and atomic absorption spectroscopic techniques

Abstract: Migration and leakage of some mobile components in rocket propellant produces an inhomogeneous composition region at which migration takes place, which can lead to premature detonation, changes in ballistic characteristics, and so on. It is, therefore, important to be able to predict the behavior of low-molecular-weight mobile additives and to control the leakage of them from the propellant. At this point, our chief interest was to study the magnitude of the migration and to understand the factors that influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Yin et al found that the change of bond strength in HTPB/toluene diisocyanate (TDI) liner affected the ingredients and contents of migration in NEPE propellant after aging by high performance liquid chromatography (HPLC) and inductively coupled plasma atomic emission spectroscopy (ICP-AES), some broke the chemical bonds, some decreased the mechanical property in the storage of HTPB/TDI liner [13]. Ünver et al found migration of a burning-rate catalyst acetyl ferrocene (AcF) in HTPB based elastomer in the presence of a plasticizer (dioctyl adipate) depending on time and temperature, and influencing by crosslink density of the barrier layer [14]. Suceska et al studied a very early stage of evaporation of nitroglycerin from a DB propellant by applying isothermal thermogravimetry experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al found that the change of bond strength in HTPB/toluene diisocyanate (TDI) liner affected the ingredients and contents of migration in NEPE propellant after aging by high performance liquid chromatography (HPLC) and inductively coupled plasma atomic emission spectroscopy (ICP-AES), some broke the chemical bonds, some decreased the mechanical property in the storage of HTPB/TDI liner [13]. Ünver et al found migration of a burning-rate catalyst acetyl ferrocene (AcF) in HTPB based elastomer in the presence of a plasticizer (dioctyl adipate) depending on time and temperature, and influencing by crosslink density of the barrier layer [14]. Suceska et al studied a very early stage of evaporation of nitroglycerin from a DB propellant by applying isothermal thermogravimetry experiments.…”
Section: Introductionmentioning
confidence: 99%
“…were recorded on a 4× microscopic melting point instrument without correction. 1 H and 13 C NMR spectra were recorded on a Bruker AV600 spectrometer at ambient temperature in CDCl 3 . Infrared spectra…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Ünver et al [49] have compared the atomic absorption spectroscopy method and ultraviolet-visible spectroscopy method in monitoring the migration of acetyl ferrocene in HTPB elastomers. Their results show that the simple and cheap technique, ultraviolet-visible spectroscopy method which requires no specimen preparation, is found to be correct enough.…”
Section: Experimental Measurementmentioning
confidence: 99%